Factorise 2y³+y²-2y-1 by using factor theorem

Answers (1)

f(y) = 2y3+y2-2y-1

Put y = 1 we get f(1) = 2+1-2-1=0

2y3+y2-2y-1 = (y-1) (2y2 -3y+1)

Put y=1 in (2y2 -3y+1) we get 2 -3+1 =0.

(y-1) is the factor of (2y2 -3y+1).

2y3+y2-2y-1 = (y-1) (y-1)(2y-1)

Preparation Products

JEE Main Rank Booster 2021

This course will help student to be better prepared and study in the right direction for JEE Main..

₹ 13999/- ₹ 9999/-
Buy Now
Rank Booster NEET 2021

This course will help student to be better prepared and study in the right direction for NEET..

₹ 13999/- ₹ 9999/-
Buy Now
Knockout JEE Main April 2021 (Easy Installments)

An exhaustive E-learning program for the complete preparation of JEE Main..

₹ 4999/-
Buy Now
Knockout NEET May 2021

An exhaustive E-learning program for the complete preparation of NEET..

₹ 22999/- ₹ 14999/-
Buy Now
Knockout NEET May 2022

An exhaustive E-learning program for the complete preparation of NEET..

₹ 34999/- ₹ 24999/-
Buy Now
Exams
Articles
Questions